FORMATION OF THE YIELD OF MELILOT UNDER THE COVER METHOD OF SOWING UNDER THE CONDITIONS OF RICE CROP ROTATION - Nurymovа, R.; Tokhetova, L.; Daldabaeva, G.; Baizhanova, B. (Ғылым және білім №2, 2020)
This article presents research on the study of elements of the technology of cultivation of melilot in the cover crop of barley. Studies have shown that the rate of sowing barley seeds in the range from 2 to 3 million seeds / ha and the nitrogen dose from 30 to 60 kg / ha are optima l, which significantly reduces the oppressive effect of cover culture, increases the survival rate of melilot plants –by 10.4-27.5%. This method of sowing contributes to the destruction of weeds, which eliminates the use of expensive herbicides and obtaining environmentally friendly products. The effective of using barley as a cover crop for perennial legumes is shown, while barley plants in the initial phase of vegetation grow very quickly and intensively and create the best conditions for the growth and development of melon on saline soils, shading them from direct sunlight. The research results were implemented in rice farms of Kyzylorda region on an area of 500 hectares, the net income was within 45.0-50.5 thousand tenge/ha, the profitability of 110%.
Keywords: рк; зерновые культуры; ячмень; высев ячменя; cover culture; melilot; fertilizer; seeding rate; survival rate